RANCANG BANGUN SISTEM MONITORING KETINGGIAN AIR BERBASIS ANDROID MENGGUNAKAN TRANSISTOR WATER LEVEL SENSOR - Arun Wiratama, Nyoman; Wiharta, Dewa Made; Ary Esta Dewi Wirastuti, Ni Made (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i04.p11, 2020)
So far, controlling the water level in the dam is still done manually by utilizing human operators, where in this case there are often mistakes in making decisions. In this research, a solution is offered in the form of an Android-based Water Level Monitoring System Design using a Water Level Sensor Transistor. There are 4 transistor water level sensors integrated with Arduino, ESP8266 module, camera module, relay, automatic water faucet, and LCD. Each sensor is used to determine the water level with 5 different states, namely Zero, Safe, Warning, Alert, and Danger. If the water level touches one of the sensors, the input given by the sensor will automatically be processed by Arduino which will then trigger a relay to open / close the water faucet and the value and status of the water level will be displayed on the LCD. After that the camera will take pictures of the water level then the ESP8266 module which functions to connect to an internet connection will help the tool to send water level data in the form of images, status, and water level values to the Android application and the Telegram application that have been installed on the Smartphone. The results obtained from this study are the design of the water level monitoring system can run well in accordance with expectations, but there are still deficiencies that can be overcome with several developments so that the design of the tool gets better results, for example by using a servo motor on the floodgate which later can make the tool work system even better.